2013
DOI: 10.1371/journal.pone.0069835
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Relationships, and Biogeography of the Lambeosaurine Dinosaurs from the European Archipelago, with Description of the New Aralosaurin Canardia garonnensis

Abstract: We provide a thorough re-evaluation of the taxonomic diversity, phylogenetic relationships, and historical biogeography of the lambeosaurine hadrosaurids from the European Archipelago. Previously published occurrences of European Lambeosaurinae are reviewed and new specimens collected from upper Maastrichtian strata of the south-central Pyrenees are described. No support is found for the recognition of European saurolophines in the available hadrosaurid materials recovered so far from this area. A new genus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
102
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(103 citation statements)
references
References 71 publications
(217 reference statements)
1
102
0
Order By: Relevance
“…Moreover, these authors estimated that nearly the 25% of the teeth from Iberian localities showed anterior denticles. However, the studied specimens differ from the tooth described by Prieto-M arquez et al (2000) in having the posterior carina placed in the medial plane of the crown and totally denticulated. The multivariate analysis carried out by Torices et al (in press) revealed clear differences among the specimen studied by Prieto-M arquez and collaborators and the remaining Iberian sample.…”
Section: Dinosaur Teethmentioning
confidence: 69%
See 3 more Smart Citations
“…Moreover, these authors estimated that nearly the 25% of the teeth from Iberian localities showed anterior denticles. However, the studied specimens differ from the tooth described by Prieto-M arquez et al (2000) in having the posterior carina placed in the medial plane of the crown and totally denticulated. The multivariate analysis carried out by Torices et al (in press) revealed clear differences among the specimen studied by Prieto-M arquez and collaborators and the remaining Iberian sample.…”
Section: Dinosaur Teethmentioning
confidence: 69%
“…The relatively small size of the denticles suggests affinity to Richardoestesia (Currie et al, 1990;Sankey et al, 2002;Llorens, 2010). MCD5033 resembles the Richardoestesia specimen from the lower Maastrichtian of the L'Abeller locality in the Eastern Tremp Syncline (Prieto-M arquez et al, 2000). However, unlike the tooth described by Prieto-M arquez et al (2000), the studied specimen has the caudal carina symmetrically placed in the crown and totally denticulated.…”
Section: Dinosaur Teethmentioning
confidence: 75%
See 2 more Smart Citations
“…The isolation from other landmasses may have facilitated the survival of relict (vicariant) taxa in Europe until Campanian-Maastrichtian times. Moreover, dispersal events between Asia (and, tentatively, between North America) and Europe have been documented during the Late Cretaceous (see Weishampel et al, 2010;Prieto-Márquez et al, 2013;Csiki et al, 2015 and references therein). The faunal exchanges that are hypothesized to occur between the Gondwanan landmasses and Europe during the Late Cretaceous are still matters of debate (Gheerbrant and Rage, 2006).…”
Section: Plesiosaursmentioning
confidence: 99%